1998
DOI: 10.1002/(sici)1097-0142(19980501)82:9<1643::aid-cncr8>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of determining des-γ-carboxy prothrombin by sensitive enzyme immunoassay in the early diagnosis of patients with hepatocellular carcinoma

Abstract: The results of this study indicate that DCP determination by sensitive enzyme immunoassay is useful in the early diagnosis of HCC because a high specificity is maintained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
104
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(108 citation statements)
references
References 20 publications
2
104
2
Order By: Relevance
“…This figure was lower than the sensitivity in the study of Mita et al (1998) (69%). In the study of Mita et al (1998), the sensitivities of HCC, small-size HCC, and well-differentiated HCC were also much higher than the sensitivities in the study of Saitoh et al (1994) and our study. Okuda et al (1999), Kuromatsu et al (1997), and Saitoh et al (1994) did not report the sensitivity of PIVKAII in the HCC patients without increased AFP, so we are unable to compare the senstivities.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…This figure was lower than the sensitivity in the study of Mita et al (1998) (69%). In the study of Mita et al (1998), the sensitivities of HCC, small-size HCC, and well-differentiated HCC were also much higher than the sensitivities in the study of Saitoh et al (1994) and our study. Okuda et al (1999), Kuromatsu et al (1997), and Saitoh et al (1994) did not report the sensitivity of PIVKAII in the HCC patients without increased AFP, so we are unable to compare the senstivities.…”
Section: Discussioncontrasting
confidence: 85%
“…The sensitivity of PIVKAII in the diagnosis of patients with HCC had been about 55% using a conventional kit (EI-test mono-P-II kit, Eisai Laboratory) before 1998. Several studies on the contrasting sensitivity kit and the conventional kit confirmed that the new kit is more sensitive than the conventional one in diagnosing HCC patients after 1998 (Mita et al, 1998;Nomura et al, 1999). The sensitivity is about 65% in patients diagnosed with HCC (Mita et al, 1998).…”
Section: Discussionmentioning
confidence: 96%
“…Finally, 17 articles were included in our study (Fig. 1, Table 1) [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84]. Eleven studies included data on more than one tumor marker [70, 71, 73-77, 79-81, 83], and 4 of them provided sensitivity and specificity of a combination of two tumor markers [70,74,77,79].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the level of AFP is elevated in patients with both HCC and chronic liver disease; thus, there is wide overlapping between the two groups [144,145]. Most studies adopt a cutoff value of 20 ng/mL for AFP, with a sensitivity ranging from 49 to 71% and specificity from 49 to 86% in HCCs smaller than 5 cm [146][147][148][149][150][151][152][153][154]. Limitations in the sensitivity and specificity of AFP in surveillance of high-risk populations have led to the use of US as an additional method for the detection of HCC [142,[155][156][157].…”
Section: What Modality Should Be Used?mentioning
confidence: 99%